Determinant of time-to-first birth interval after marriage among Ethiopian women - Chernet, Ayele Gebeyehu (BMC Womens Health, 2019)
BACKGROUND: Time-to-first birth after marriage has a significant role in the future life of each individual woman and has a direct relationship with fertility. This study aimed to see the determinant of time-to-first birth interval after marriage among Ethiopian women. METHODS: The data was obtained from 2011 Ethiopia Demographic and Health Survey which is the third survey. The sample was selected using a stratified; two-stage cluster sampling design and the data was analysed using parametric shared frailty model. RESULTS: A total of 7925 ever married women from the nine region of the country were included in this study. Of the total women, 5966 (75.3%) of them gave firstbirth. Age, residence area, employment status, contraceptive use and education of women were associated significantly to time-to-first birth. CONCLUSIONS: Women having younger age at first marriage, urban women, contraceptive users had prolonged time to first birth interval. There is a need of teaching family for contraceptive use and improving women education to increase the length of first birth interval in Ethiopia.